Pectin characterization and factors affecting pectin extraction from Citrus grandis L. Osbeck (Pummelo) peels - Ismail @ Khori, Noor Jannah Firdouse (2015)
Microwave-assisted extraction (MAE) and ultrasound-assisted extraction (UAE) have been developed to increase the yield and quality of various plantbased constituents with shorter time of extraction. This research aimed to study the effect of four (4) factors towards the quantity and quality of pectin extracted from pummelo peels, using two (2) level factorial designs, utilizing UAE, MAE and water bath extraction (WBE) methods. Factors manipulated were time, pH, sample-to-solvent ratio and temperature. MAE, UAE and conventional methods were able to extract pectin up to 78.98 % in a minute, 38.7% in 10 minutes and 68.26% in 30 minutes, respectively. Pectin from MAE method significantly has the highest DE (60.41 ± 0.37) followed by WBE method (55.99 ± 1.22) and UAE method (54.64 ± 0.503). The galacturonic acid (GalA) content of pectin extracted using MAE was significantly the highest (82.71% ± 1.77) compared to UAE and WBE methods (67.37 ± 1.88 and 55.99 ± 1.22 respectively). This study showed that pummelo peels of Ledang variety contained high methoxyl pectin (DE > 50%) with GalA content of more than 65%. MAE was the most efficient method to produce high methoxyl pectin with high content of GalA.